The Effects of Delivery Mode on the Gut Microbiota and Health: State of Art - Zhang, Chenchen; Li, Lixiang; Jin, Biying; Xu, Xinyan; Zuo, Xiuli; Li, Yanqing; Li, Zhen (Frontiers in Microbiology, 2021)
The delivery mode is an important factor driving alteration in the gut microbiota during the neonatal period. Several studies prove that the alteration of gut microbiota induced by cesarean section could influence the activation of intestinal epithelial cells and the development of immune system. Probiotics could promote the intestinal microecology, which may further prevent and treat cesarean section related diseases. All of these are of great significance to provide a clinically feasible method for the prevention and treatment of cesarean section related gut diseases. This review summarizes some autoimmune and metabolic disorders which may be caused by dysbiosis of gut microbiota in infants delivered by cesarean section.